PENDIDIKAN GERAK BULUTANGKIS - Sugiharto, - (Lembaran Ilmu Kependidikan, 2008)
Badminton Movement Training is a compulsory subject that each scholar in the faculty of Sport Science, Sport Trainer Education, and Physical Health and Recreation Education at FIK UNNES Semarang must pass. The basic techniques in badminton movements training includes the technique of holding rackets, behavior and position, forehand stroke, backhand stroke, smash preparation, and stroke variation. Badminton is full of complex abilities and skills. Therefore, it is important to a badminton player to have best physical performance, and this can be gained only through a well and continuous programmed physical training so that the badminton player can have his or her best physical performance. This will give positive effect to his or her mental and psychic condition, and eventually affects to the performance of his or her playing technique directly. Training will affect both nervous and muscles system. To the nervous system, the effect of the training is to repair and to develop the structure and the function of synapses so their physiology grows better. Training movement pattern will also be recorded in the brain nervous system as motor-engram. The motor-engram will control musclesÃ¢â¬â¢ activities, especially those which need high skill. Motor engram can be increased by repeated training and can be decreased at the retirement from an exercise. Kata kunci: Pendidikan gerak bulutangkis, kondisi fisik, faali, motor-engram